2016
DOI: 10.1111/medu.12937
|View full text |Cite
|
Sign up to set email alerts
|

A multi-site study of strategies to teach critical thinking: ‘why do you think that?’

Abstract: This work has practical recommendations for the individual faculty member. Promoting higher-level cognition, asking questions that probe the learner's understanding and linking discussions to the clinical context are some of the approaches that can be incorporated immediately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 25 publications
(43 reference statements)
0
37
0
6
Order By: Relevance
“…According to Littlewood: teachers' feedback is an important act in English teaching because it "provide learners with knowledge of how successful their performance has been and has a great influence on students' interests in learning English" [11][12][13]. That is, after students' answering, teachers should give students corresponding evaluations.…”
Section: Lack Of Corresponding Feedbacksmentioning
confidence: 99%
“…According to Littlewood: teachers' feedback is an important act in English teaching because it "provide learners with knowledge of how successful their performance has been and has a great influence on students' interests in learning English" [11][12][13]. That is, after students' answering, teachers should give students corresponding evaluations.…”
Section: Lack Of Corresponding Feedbacksmentioning
confidence: 99%
“…More specifically, probing questions facilitate the process of critical thinking (Huang et al, 2016). They help extend students' thinking by encouraging them to consider their own learning and knowledge (Huang et al, 2016).…”
Section: Creating Questionsmentioning
confidence: 99%
“…Brookfield (2012) stated that faculty could model critical thinking by sharing personal examples from their own academic and professional work, or by providing context for the content by explaining why they did what they did. Huang et al (2016), researching how healthcare faculty teach critical thinking, found that those who were successful used modeling as an instructional method to show students a path for engaging in it themselves. Faculty members used modeling to teach questioning strategies, reflection writing, or other activities.…”
Section: Modelingmentioning
confidence: 99%
See 2 more Smart Citations